Profil Maternal pada Kasus Kematian Neonatus di Rumah Sakit Umum Daerah (RSUD) Ciawi - Ity Sulawati; Dean Ascha Wijaya; William Gilbert Satyanegara (Pusat Riset dan Inovasi Nasional, 2023)
In 2013, 4.6 million babies died worldwide before their first birthday, with 50% dying on the first day and nearly 75% within the first week. Most stillbirths and premature newborn deaths are attributable to birth complications that are preventable. The maternal profile in neonatal mortality cases plays an important role in understanding the factors that contribute to this high mortality rate. This cross-sectional study aims to determine the maternal profile of neonatal death cases at Ciawi Hospital, which were selected according to the criteria by total sampling based on medical record data from January 1, 2020, to December 31, 2020. The variables utilized in this study include maternal factors such as gestational age, type of delivery, twin pregnancy, presentation of pregnancy, medical condition of the mother, and obstetric problems. The data is presented in a descriptive format. Among the 58 respondents, the average age was 30.26 years, with a higher prevalence of preterm births (55.2%). The most frequently encountered medical condition in the maternal profile of neonatal deaths at Ciawi General Hospital is chronic hypertension. Conversely, the most common obstetric problems are premature rupture of membranes and oligohydramnios. Efforts to address medical issues in mothers can contribute to the reduction of neonatal mortality cases.